Respiratory Severity Score and Oxygen Saturation Index during the First 2 Hours of Life as Predictors for Noninvasive Respiratory Support Failure in Respiratory Distress Syndrome - Zapata, Henry A.; Koueik, Jack; Becker, Heather L.; Lasarev, Michael R.; Guthrie, Scott O.; Kaluarachchi, Dinushan C. (American Journal of Perinatology, 2024)
Objective Noninvasive respiratory support (NRS) failure is common in preterm infants with respiratory distress syndrome (RDS). We evaluated the utility of respiratory severity score (RSS) and oxygen saturation index (OSI) during the first 2 hours of life (HOL) as predictors for NRS failure in moderate preterm infants.Study Design We conducted a retrospective cohort study of infants born between 280/7 and 336/7 weeks with RDS. Univariate and multivariable logistic regression analyses were used to assess whether the RSS and OSI summary measures were associated with NRS failure.Results A total of 282 infants were included in the study. Median gestational age and birth weights were 32 weeks and 1.7 kg, respectively. Fifty-eight infants (21%) developed NRS failure at the median age of 10.5 hours. RSS and OSI summary measures in the first 2 HOL were associated with NRS failure within 72 HOL.Conclusion RSS and OSI during the first 2 HOL can predict NRS failure. Optimal RSS and OSI cutoffs for the prediction of NRS failure need to be determined in large cohort studies.Key Points
Keywords: respiratory distress syndrome; surfactant; noninvasive respiratory support failure; CPAP; respiratory severity score; oxygen saturation index